PELAS LENTES DA TELEVISÃO UNIVERSITÁRIA: A REPRESENTAÇÃO SOCIAL DA UNIVERSIDADE FRANCISCANA E A EDUCAÇÃO MIDIÁTICA NA UFN TV - Taschetto, Bruna (2024)
This dissertation analyzes the role of University Television (UTV), with a focus on UFN TV and the program Universo Acadêmico, as a tool to promote Media Education and strengthen the social representation of the Franciscan University (UFN). The qualitative study is structured into three complementary articles addressing the central question: how does UFN TV use visibility, legitimization, and valorization strategies to construct and reinforce the university's image while promoting Media Education? The first article establishes the relationship between University Television and Media Education through a bibliographical review, identifying synergies between the fields and highlighting UTV’s potential to cultivate critical and informed citizens in an era dominated by misinformation. The second article examines the communication strategies employed by the Universo Acadêmico program, analyzing its content and practices to demonstrate how UFN TV buildsits social representation by disseminating scientific, cultural, and institutional activities. The third article delves into the program's role in promoting Media Education, assessing its ability to foster critical consumption of information and proposing strategies to strengthen this practice in the current media ecosystem. The findings reveal that UFN TV employs images, expert testimonies, and relevant topics to enhance the university's visibility and legitimize its initiatives. Furthermore, the program incorporates Media Education principles, encouraging reflections on the role of media and its societal influence. The study concludes that University Television, with its educational nature and independence from commercial interests, serves as a strategic tool to amplify the social impact of academic institutions by promoting citizenship, critical thinking, and institutional appreciation. The article- based structure underscores the interdisciplinary nature and relevance of the research, emphasizing UFN TV's contribution to contemporary communication and education.